Merging toughness and oxidation resistance in a light ZrB2 composite. (5th December 2019) - Silvestroni, Laura; Melandri, Cesare; Venkatachalam, Vinothini; Binner, Jon; Sciti, Diletta
Abstract: A functionally graded composite based on ZrB2 and 0–50 vol% of short carbon fibres was prepared via a deliberately simple approach that involved creating a suitable stacking sequence of layers with different sintering agents and fibre contents. This led to an excellent combination of failure tolerance and oxidation resistance in a light material with a density below that of alumina. The graded architecture outperformed other related composites when tested at 1500 °C and, separately, achieved a toughness of 10 MPa m ½ . In addition, the composite withstood the ablation effect of an oxyacetylene torch at 2500 °C, undergoing minimal recession. Moreover, the true nature of the "tubular" zirconium oxide formed upon oxidation at extreme temperatures is reported for the first time. The functionally graded concept applied to a ultra-refractory matrix seems to be a promising route to obtain even complex shaped components with functional symmetry for use in severe environments. Graphical abstract: Unlabelled Image Highlights: A functionally graded composite (FGC) based on ZrB2 and 0 - 50 vol% short C fibres was obtained by hot pressing. The FGC overcome the trade-off between strength and toughness at high temperature achieving 10 MPa m ½ at 1500°C. The FGC withstood an oxyacetylene test at 2000-2500°C undergoing minimal recession. The FGC approach combines excellent failure tolerance and oxidation resistance in a lightweight material. The FGC hierarchical structure surpassed the resistance to damages and to extreme environments of traditional UHTCs.